COVID-19 Measures and Human Dignity in Colombia: Restrictions of Fundamental Rights in Bogotá and Valle de Aburrá during the March-June 2020 Period - Gladis Cecilia Villegas Arias (Opinión Jurídica)
The goal of this article is to analyze the impact that the regulations issued under the national lockdown declared by the Colombian government during the crisis caused by COVID-19 had on human dignity. A qualitative analysis inspired on the methodology of regulatory impact analysis was applied to secondary data extracted from publications by the World Health Organization (WHO); the national government of Colombia; the local governments of Bogota and the municipalities included in the Metropolitan Area of the Aburra Valley; as well as to news published in relevant newspapers of the country during the episode under study. Results indicated that perceptions of legitimacy of institutions, ability to make decisions, sources of material life, social interactions, social controls, relationships to space, mental health, and controls over the body, were aspects of human dignity negatively impacted by the ruling during this episode. The main conclusion of this article is that citizens of Colombia under the ruling of biology lost many rights that the species had gained for protecting human dignity.